Ongula ngee twa penduka : Illuminating futures perspective of student teachers on the future of the Oshiwambo language - Akwaake, Abius (My University, 2025)
Oshiwambo, is a living indigenous language within Namibia’s multilingual and multicultural landscape. Despite its sociocultural significance, it faces increased marginalisation propelled by the forces of globalisation and urbanisation. The national language policy prioritises English as the primary medium of instruction in schools. The use of Oshiwambo is in decline particularly among younger generations who increasingly favour English for their education and economic mobility and social interaction. Using an exploratory qualitative participatory approach this study combines ethnography with futures research methods, to explore the perspectives of 53 student teachers on the possible trajectory of the Oshiwambo language by 2054. The study uses Causal Layered Analysis (CLA) in futures workshops combined with ethnographic observations to study and explore this topic. Teachers of indigenous languages offer important insights into the processes of language transmission, loss, and revitalisation in multilingual and multicultural societies and therefore, their views on the future of the language they intend to teach provide critical insights on broader sociolinguistic dynamics. The study, further, explores the complex interplay of language policy, societal attitudes, ecological sustainability, and the ongoing technology advances shaping the trajectory of the Oshiwambo language. Although multilingualism is celebrated in developmental discourse, African languages remain increasingly confined to informal domains, reinforcing patterns of systemic marginalisation. The study affirms this complex paradox, as participants assert that, while Oshiwambo is deeply valued as a symbol of cultural identity, it remains marginalised in both everyday communication and in institutional settings. While this study is personally motivated, it is partly informed by a distinct lack of futures research and methodologies studies on Namibian languages. It provides scholars a framework for deconstructing complex societal issues with a foresight perspective. By exploring both optimistic and pessimistic views of the future, the study identifies key drivers and opposing forces influencing the trajectory and sustainability of the Oshiwambo language. Cultural resilience, ecological knowledge, and the innovative use of technology emerged as promising avenues for language revitalisation. In contrast, societal neglect, policy inertia and balancing individual choice with emerging global trends were seen as forces accelerating language decline. The results highlight young educators’ agency and capacity to reimagine language futures underscoring the critical role of intergenerational transmission in sustaining the indigenous African language futures. This study contributes to the broader discourse on indigenous language sustainability. It reveals how intergenerational agency, the awareness of plurality of futures, and most importantly the application of creativity in engaging with technologies can inform innovative language revitalisation strategies. It underscores the need for dynamic, community-rooted approaches that reimagines Oshiwambo as a living, evolving language - capable of thriving within Namibia’s shifting sociocultural and technology landscape.

Oshiwambo, shoka shi li elaka li na omwenyo muNamibia ngoka e li oshilongo shi na omalaka nomithigulukwakalo dha yoolokathana. Nonando shi na esimano lyopankalathano nopa-muthigululwakalo wo osha taalela okudhinwa. Eyunipaleko, endoolopaleko, omilandu dho-pashigwana dhelaka dhoka dha tula komeho/koshiyalo. Elongitho lyOshiingilisa ongelaka lyomalo-gelo nolyopambelewa oyo naanaa tayi endeleleke egwopevi lyelaka ndi, unene maapopi yalyo aagundjuka mboka taa tsikile noku li yambidhidha omolwelongo nomolwomahupilo. Epekapeko ndika otali longitha omukalo gwomakonakono gopauvalelwamo, nomapekapeko gomonakuyiwa/gomatalikomeho okukonakona onkalo yelaka lyOshiwambo oku ka thika ko2054 oku shi talela pamayiuvo gomulongwalongi. Epekapeko olyo tuu ndika otali konakona nkene omulandu gwelaka, omaiyuvo gaakwashigwana, ehumokomeho lyuungomba nuutekinolohi, osho wo elongitho lyomalaka gopaigwana tayi nwetha mo onkalo yelaka ndika. Omanga elongitho lyomalaka ogendji tali nyanyukilwapwaa na okutula milonga, omalaka gOshiAfrika onkee ngaa haga kala ga ngambekelwa koonkalo inadhi ihwa po, shoka hashi fala mokuthigwa po. Aapopi yelaka aagundjuka onkee ngaa taa tsikile nokusimaneka Oshiingilisa omolwelongo nosho wo molwomahupilo, shoka tashi fala Oshiwambo monkalo ondhigu okuuva ko moka lya simanekwa ongedhidhiliko lyopamuthigululwakalo ihe olya dhinika pakulongithwa. Epekaapeko ndika otali longitha omukalo omupe gwo CLA okulalakanena okutala konakuyiwa, pwaa na omalimbililo ihe opena eyikwatopomutima, mokuvongokonona mboka ya simana moku-tunga po ekalekepo lyOshiwambo. Aalongi yomalakaoyo yeli yasimana unene mokulandula nokunjdandjukununa ngene elaka hali ilongwa, okutaandelithwa nenge okuli kanitha po. Mokulongitha epekaapeko ndika lyokutala komeho, otaku ka yelithwa mo nawa ependulepo nekalekepo lyelaka lyOshiwambo moNamibia. Omanga epekaapeko ndika olyopaumwene, otali mono mo woo kutya omaiyuvo gaapopi yelaka kombinga yalyo osho wo omatsomukumo ga ngambekwa oyo iiyetithi yeikwatopomutima, omanga iikwamuthigululwakalo oyo tayi humitha komeho omadhiladhilo nomaiyuvo omawanawa kombinga yelaka muulethimbo. Elongitho lyiikwaungomba nomakwatathano oyo omikalo / iilongitho iiwanawa mekalekepo lyelaka. Iizemo yepekapeko otayi gwedha ko wo koonkundathana dha mbwalangandja kombinga yomulandu gwelaka, ehumithokomehonawa lyomuthigululwakalo, nonkandangala yomalaka gaavalelwamo mehumokomeho lyaAfrika,nokugandja uuyelele mekuthombinga ndyoka tali shilipaleke ompumbwe tayi tsikile yOshiwambo momimvo dhomilongo tadhi ya. Otashi tende omuthindo ompumbwe yo ku etapo omikalo dha guma aakwashigwana oku lundulula nkene ya taalela onakuyiwa yelaka lyoshiwambo, li kale lina omwenyo lyo li tsikile nokuhuma komeho moNamibia yo nakuyiwa ndjoka ya taalela ehumo komeho monkalathano no pautekenika.
Keywords: Indigenous languages, Oshiwambo, Language policy, Language revitalisation, Futures studies, Causal Layered Analysis, Narrative analysis, Cultural sustainability, Omalaka gaavalelwamo, Oshiwambo, Omulandu gwelaka, ekolekululo lyelaka, Eilongo lyonakuyiwa, CLA, Efatululo, Omuthigululwakalo gwiixwapo